Rosmarinus officinalis Essential Oil Improves Scopolamine-Induced Neurobehavioral Changes via Restoration of Cholinergic Function and Brain Antioxidant Status in Zebrafish (Danio rerio) - Luminita Capatina; Razvan Stefan Boiangiu; Gabriela Dumitru; Edoardo Marco Napoli; Giuseppe Ruberto; Lucian Hritcu; Elena Todirascu-Ciornea (MDPI AG, 2020)
Rosmarinus officinalis L. is a traditional herb with various therapeutic applications such as antibacterial, antioxidant, anti-inflammatory, antidepressant, and anticholinesterase activities, and can be used for the prevention or treatment of dementia. In the present study, we tested whether Rosmarinus officinalis L. could counteract scopolamine-induced anxiety, dementia, and brain oxidative stress in the zebrafish model and tried to find the underlying mechanism. Rosmarinus officinalis L. essential oil (REO: 25, 150, and 300 µL/L) was administered by immersion to zebrafish (Danio rerio) once daily for eight days while scopolamine (100 µM) treatment was delivered 30 min before behavioral tests. The antidepressant and cognitive-enhancing actions of the essential oil in the scopolamine zebrafish model was measured in the novel tank diving test (NTT) and Y-maze test. The chemical composition was identified by Gas chromatograph−Mass spectrometry (GC-MS) analysis. The brain oxidative status and acetylcholinesterase (AChE) activity was also determined. REO reversed scopolamine-induced anxiety, memory impairment, and brain oxidative stress. In addition, a reduced brain AChE activity following the administration of REO in scopolamine-treated fish was observed. In conclusion, REO exerted antidepressant-like effect and cognitive-enhancing action and was able to abolish AChE alteration and brain oxidative stress induced by scopolamine.